The existence and stability of smooth solutions for multidimensional isentropic bipolar hydrodynamic model of semiconductors. (October 2019) - Liu, Lingjun
Abstract: The present paper is concerned with the existence and stability of smooth stationary solutions to the multidimensional isentropic bipolar hydrodynamic model for semiconductors in a bounded domain Ω ∈ R N ( N = 1, 2, 3 ) with insulating boundary conditions. The existence of non-constant steady smooth solutions is firstly obtained by the calculus of variations and the maximum principle. It is further shown that the particle densities converge exponentially fast to the steady state solutions.